PEMAKNAAN COVER MAJALAH TEMPO (Analisis Semiotika Cover Majalah Tempo Edisi 16 September-22 September 2019) - Noval Setiawan (SOURCE : Jurnal Ilmu Komunikasi, 2020)
AbstractThe study entitled "The Meaning of Tempo Magazine Cover (Semiotic Analysis of Tempo Magazine Cover September 16-September 22 2019, entitled Promise Staying Promise)" aims to find out the meaning of the meaning of the magazine cover tempo "Promise Stay Promise" seen from the meaning of illustrations, texts and color on the magazine cover. The method used in this research is descriptive qualitative method with Roland Barthes's semiotic analysis approach, which examines signs through three stages of analysis namely denotation, connotation, mythology.The results of this study might reveal that the magazine cover of this edition shows the properties possessed by Mr. Jokowi as seen from the depiction of the face shape in the illustrations. The meaning of denotation, both the meaning of shadow, clothing and expression is illustrated, that the tempo magazine is a critical medium with the constitution and the spirit of democracy. While the connotation of the illustration is about the public's expectation of the revision of the KPK Law. As for the characteristics of President Jokowi's expression with his eyes closed and lips purely expressing something and his nose stretching out, that Mr. Jokowi is a liar. Furthermore, the mythological meaning found behind the illustration is a picture that contains assumptions about the unrelated Jokowi's promises and the President's responsibility towards the Revision of the KPK Law. Then in the headline and subheadline text and the black color in the nose's shadow, there is a provocation in it related to the ideology of the tempo magazine. The conclusion of this study, that the visual images contained in the magazine cover tempo "Promise Staying Promise" consisting of illustrations, text, and colors have a meaning contained therein. Keywords: Tempo Magazine Cover, Illustration, Semiotics Roland Barthes.